Educational Internship Analysis Using CIPP Model in the Economic Education Study Program - Jaryono, Jaryono; Indrayanto, Adi; Tohir, Tohir; Krisnaresanti, Aldila (Economic Education Analysis Journal, 2021)
The Educational Internship Program is a form of self-actualization for those who have received various educational theories ranging from codes of ethics and the teaching profession, classroom learning planning, making learning instruments, classroom management to learning evaluation. This research is a qualitative descriptive study that aims to analyze the implementation of Educational Internships Economic Education students at Jenderal Soedirman University in Senior Highschool and Islamic Senior Highschool in Banyumas Regency in terms of (1) Study Program Readiness in the Implementation of Educational Internships (2) School readiness in implementing Educational Internships (3) Students' readiness in implementing Educational Internships. The subjects in this study were Lecturers in the Economics Education Study Program, students who had carried out educational internships, teachers and students from SMA and MAN in Banyumas Regency which became the internship places for economic education students. The sampling technique used was purposive sampling method. The research respondents included 8 civil servant teachers, 8 principals, 7 supervising lecturers, 48 students participating in educational internships, and 40 students who had been taught by practical students. Data was collected using in-depth interview, Focus Group Discussion (FGD) observation and documentation techniques. The results of data collection were then analyzed using interactive model analysis techniques consisting of data collection, data reduction, data presentation, data quality testing, and drawing conclusions. In addition, the data obtained were analyzed using the CIPP model analysis (context, input, process, and product) which is a comprehensive evaluation mode based on its components.